Groups with infinitely many ends acting analytically on the circle. Issue 4 (24th June 2019) - Alvarez, Sébastien; Filimonov, Dmitry; Kleptsyn, Victor; Malicet, Dominique; Meniño Cotón, Carlos; Navas, Andrés; Triestino, Michele
Abstract: This article is inspired by two milestones in the study of non‐minimal group actions on the circle: Duminy's theorem about the number of ends of semi‐exceptional leaves, and Ghys' freeness result in real‐analytic regularity. Our first result concerns groups of real‐analytic diffeomorphisms with infinitely many ends: if the action is non‐expanding, then the group is virtually free. The second result is a Duminy type theorem for minimal codimension‐one foliations: either non‐expandable leaves have infinitely many ends, or the holonomy pseudogroup preserves a projective structure.